Effectiveness of Sign-Based Videos on English Comprehension of Students with Hearing Impairment - Ishrat, Ghazala; Bano, Humara; Qureshi, Maria Sohaib (Annals of Human and Social Sciences, 2024)
This study investigates the efficacy of sign-based video interventions in improving English Comprehension among fifth-grade students with hearing impairments (SWHI). This study aims to develop and assess the effectiveness of a sign-based video intervention in improving the English reading skills of 5th-grade SWHI. The study employed a quasi-experimental approach, selecting 30 students from a private institute using a non-equivalent control group design. The English Reading Test (ERT) was given as a pretest and post-test to assess learning outcomes. To ensure a high level of dependability, pilot testing was conducted with an additional 30 students, resulting in a reliability coefficient of .845. The research findings indicate that using technology-enhanced teaching approaches, such as sign-based video Intervention, substantially positively impacts independent reading and concept clarification. These methods also promote motivation and improve long-term memory. It recommend to adapt other subjects for better comprehension of SWHI and integrate technology.